Three Propositions on African Economic Growth - Dhonte, Pierre (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1995)
This paper describes the African economic growth and asserts the establishment of a growth-conducive environment is the unifying purpose of the IMF's extensive involvement in Africa. A major purpose of the IMF's extensive involvement in Africa is to promote high quality growth. As to the specific basis for the IMF's original perspective on growth, it may be found in the debate that followed the debt crisis of the 1980s, when the concrete relevance of growth as a determinant of the sustainability of balance-of-payments positions and of the viability of a country's payments system became evident. Although the elimination of financial instability is essential to remove trade restraints, and thereby to promote growth, growth in turn is necessary if trade restraints are to be averted. The point of anchoring the domestic system of relative prices to the international system through open trading and an equilibrium exchange rate is to provide signals that will guide the efficient utilization of domestic resources; the whole approach becomes pointless if these signals are blocked by domestic price regulation.